Analisis Sitiran Terhadap tugas Akhir Mahasiswa Program Studi Ilmu Informasi Perpustakaan dan Kearsipan Fakultas Bahasa dan Seni Universitas Negeri Padang Tahun 2010-2012 - St., Zulmaisar; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This paper focuses on formulating the problem , namely , (1) the author of the most widely cited by students of Library and Information Science Archives . (2) library materials most widely cited by students of Library and Information Science Archives . (3) the subject of the most written by students of Library and Information Science Archives . This research method is descriptive in this study illustrate the types of literature and the literature cited dominant . This study uses the entire population Prodi Final IIPK years 2010-2012 a total of 147 papers . Data collection methods used in this research is a method of citation analysis . In this study, the data used is citation citation contained in the bibliography of each paper , which will be created for the table . Based on the data analysis we can conclude (1) the author of the most widely cited is Sulistyo - basuki the number of citations 147 pieces were taken first rank . (2) library materials are frequently cited by the number of books a student is 1,708 pieces citation needed in the first rank . (3) on the subject of the most widely cited is the processing of library materials by the number of citations 29 pieces are in the first rank are written by students Prodi IIPK.